2011
DOI: 10.1007/s10654-011-9564-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and risk of acute coronary syndrome and mortality in men and women with and without hypertension

Abstract: Although a light to moderate alcohol intake is associated with a lower risk of acute coronary syndrome (ACS), alcohol is also associated with risk of hypertension, which in turn is a strong risk factor of ACS. We examined whether middle-aged men and women with hypertension also benefit from a light to moderate alcohol intake in relation to risk of ACS and overall mortality. We used data from 57,053 men and women, aged 50-64, who participated in the Danish Diet, Cancer and Health study. Information on alcohol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Meta-analysis of the results from three major UK cohorts together with those from 12 published studies found J-curve relationships between alcohol consumption and mortality in those with cardiovascular disease, with the greatest risk reduction being observed at 7 g/day for all-cause mortality and 8 g/day for cardiovascular mortality relative to current non-drinkers. This dose-response trend remains consistent with the last published meta-analysis [ 10 ] and has also been reported in other high-risk populations, such as hypertensive [ 57 ] and diabetic individuals [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Meta-analysis of the results from three major UK cohorts together with those from 12 published studies found J-curve relationships between alcohol consumption and mortality in those with cardiovascular disease, with the greatest risk reduction being observed at 7 g/day for all-cause mortality and 8 g/day for cardiovascular mortality relative to current non-drinkers. This dose-response trend remains consistent with the last published meta-analysis [ 10 ] and has also been reported in other high-risk populations, such as hypertensive [ 57 ] and diabetic individuals [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…An inverse relationship was found between alcohol intake and acute coronary syndrome . Moderate drinking was associated with a lower mortality rate than abstaining or heavy drinking . Similar confusing results were found in diabetes mellitus, incident HF, and ischemic and hemorrhagic stroke .…”
Section: Self‐care Behaviorsmentioning
confidence: 52%
“…Moderate drinking was associated with a lower mortality rate than abstaining or heavy drinking . Similar confusing results were found in diabetes mellitus, incident HF, and ischemic and hemorrhagic stroke . Given the potential negative health and societal consequences of alcohol dependence or abuse, people who do not currently drink alcohol should not be encouraged to begin drinking.…”
Section: Self‐care Behaviorsmentioning
confidence: 75%
See 1 more Smart Citation
“…The association between alcohol consumption and diabetes risk is unclear, and counterintuitive findings of greater rates of diabetic patients among abstainers and light drinkers have been reported in French [ 51 ], Danish [ 52 ], and US populations [ 43 , 53 ]. These findings may be attributed to diabetes patients’ tendency to cease or minimize drinking alcohol as prescribed by their doctors.…”
Section: Discussionmentioning
confidence: 99%